Adult educators' core competences - Wahlgren, Bjarne (International review of education, 2016)
Which competences do professional adult educators need? This research note discusses the topic from a comparative perspective, finding that adult educators' required competences are wide-ranging, heterogeneous and complex. They are subject to context in terms of national and cultural environment as well as the kind of adult education concerned (e.g. basic education, work-related education etc.). However, it seems that it is possible to identify certain competence requirements which transcend national, cultural and functional boundaries. This research note summarises these common or "core" requirements, organising them into four thematic subcategories: (1) communicating subject knowledge; (2) taking students' prior learning into account; (3) supporting a learning environment; and (4) the adult educator's reflection on his or her own performance. At the end of his analysis of different competence profiles, the author notes that adult educators' ability to train adult learners in a way which then enables them to apply and use what they have learned in practice (thus performing knowledge transfer) still seems to be overlooked. Compétences fondamentales des éducateurs d'adultes – De quelles compétences ont besoin les éducateurs d'adultes professionnels? Cette note de recherche analyse le sujet dans une perspective comparée et constate que les compétences requises chez les éducateurs d'adultes sont diversifiées, hétérogènes et complexes. Elles dépendent du contexte en terme d'environnement national et culturel ainsi que du type d'éducation des adultes concerné (enseignement de base, enseignement professionnel, etc.). Néanmoins, il semble possible d'identifier des compétences indispensables qui dépassent les frontières nationales, culturelles et fonctionnelles. La présente note de recherche synthétise ces exigences communes ou fondamentales, en les classant selon quatre sous-catégories thématiques : 1) communiquer des connaissances sur un sujet, 2) tenir compte des acquis des apprenants, 3) favoriser un environnement propice à l'apprentissage, et 4) mener une réflexion sur sa prestation d'éducateur/trice d'adultes. À l'issue de son analyse des différents profils de compétences, l'auteur relève qu'une capacité semble aujourd'hui encore négligée chez les éducateurs d'adultes : celle consistant à former les apprenants adultes de telle sorte qu'ils puissent appliquer et utiliser dans la pratique ce qu'ils ont appris (réalisant ainsi un transfert de connaissances).